QUALITY EVALUATION OF FUNCTIONAL BREAD FROM WHEAT, CARROT, TILAPIA, AND HERRING FISH FLOUR BLENDS - Agiriga, Anna Ngozi; Iwe, Maduebibisi Ofo; Otenaike, Tobiloba Adedeji; Ayeni, Oluwatayo David; Okoro, Chidi Immaculate (FUDMA JOURNAL OF SCIENCES, 2025)
The production and evaluation of bread from flour blends comprising wheat, carrot, tilapia, and herring fish were investigated. 100% wheat flour (WF100) was the control. Seven bread samples were formulated: a control (SWF100) and six composite variations with increasing substitution levels of carrot, tilapia, and herring fish flours. Functional properties of the flour samples were determined. Proximate, physical, and sensory properties of the bread samples were evaluated. The water absorption capacity of the blends ranged between 78.67g/ml to 104.33g/ml, oil absorption capacity, 73.33g/ml to 83.33g/ml; bulk density, 0.73g/cm3 to 0.83g/cm3; foaming capacity, 3.60% to 5.13%; and solubility, 11.67% to 14.35%. The moisture content of the bread samples ranged between 24.53% to 34.40%, protein, 14.49% to 16.94%; fat, 3.17% to 4.83%; ash, 2.10% to 3.41%; fibre, 0.40% to 0.50%; and carbohydrates, 40.67% to 54.71%. The weight of the bread samples ranged from 221.27g to 233.70g, length, 18.50mm to 21.17mm; and width, 12.33mm to 14.00mm. Bread samples from WF100 had the lowest value in all the nutritional attributes analyzed (protein, 9.24%; fat, 2.17%; ash, 0.57%; fibre, 0.33%), but the highest carbohydrate content (63.56%). The functional bread samples compared favorably with SWF100 in all the sensory attributes assessed. Bread samples from wheat (90%), carrot (5%), and herring fish (5%) (SWCH90:5:5), were the most acceptable with an overall acceptability score of 7.70 and compared favorably with SWF100 with an overall acceptability score of 7.95. The functional breads offer a nutritious alternative to wheat bread and can help address nutritional deficiencies in vulnerable populations.